Organizational support and job satisfaction: Meta-analysis study - Yuwono, Susatyo (Indigenous, 2021)
Abstract. This study aims to determine the relationship between organizational support and job satisfaction. Using the meta-analysis approach, the hypothesis is proposed that there is a relationship between organizational support and job satisfaction. Previous studies used 19 articles containing 22 research results that have F, t, d, and r values. The total sample obtained was 11,257 samples with various backgrounds. The analysis show that the population correlation coefficient after being corrected by the number of samples is 0.57. Referring to the 95% significance level, the acceptance limit is between 0.3687 r 0.7648. Thus the results of 0.57 are at the acceptance limit. Based on these results, it can be concluded that the hypothesis that there is a relationship between organizational support and job satisfaction is acceptable. These results strengthen the relationship between organizational support andjob satisfaction.Keywords: organizational support, job satisfaction, meta-analysis